2018
DOI: 10.1123/ijsnem.2017-0407
|View full text |Cite
|
Sign up to set email alerts
|

Multiday Pomegranate Extract Supplementation Decreases Oxygen Uptake During Submaximal Cycling Exercise, but Cosupplementation With N-acetylcysteine Negates the Effect

Abstract: Pomegranate extract (POMx) has been suggested as an ergogenic aid due to its rich concentration of polyphenols, which are proposed to enhance nitric oxide bioavailability, thereby improving the efficiency of oxygen usage and, consequently, endurance exercise performance. Although acute POMx supplementation improves aerobic exercise performance in untrained individuals, trained athletes appear to require chronic supplementation for a similar effect. Furthermore, the combination of POMx with a thiol antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…As shown in Additional Material 3, only five polyphenol studies included a direct measure of nitric oxide status (e.g. plasma NO 3 - or NO 2 - ), with only one study [ 149 ] demonstrating a significant increase in any of these biomarkers (plasma NO 3 - ) following polyphenol (pomegranate) consumption. Similarly, only 14 polyphenol studies investigated effects on vascular parameters such as flow-mediated dilation (FMD) and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Additional Material 3, only five polyphenol studies included a direct measure of nitric oxide status (e.g. plasma NO 3 - or NO 2 - ), with only one study [ 149 ] demonstrating a significant increase in any of these biomarkers (plasma NO 3 - ) following polyphenol (pomegranate) consumption. Similarly, only 14 polyphenol studies investigated effects on vascular parameters such as flow-mediated dilation (FMD) and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…NO regulates physiological functions and has been recognized as an important factor in endothelial vascular relaxation during exercise [46,47,48] which also increases muscle blood flow [49]. Pomegranate significantly increase plasma nitrate (NO 3 ) when supplemented for 8 days [50]. In addition, other polyphenol-rich supplements can produce a similar vasodilatation and contribution to NO pathways [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited research investigating these possible mechanisms in athletes. One study investigating the influence of multi-day pomegranate extract co-supplemented with NAC in male cyclists rejected the study hypothesis that it originally suggested, suggesting that co-supplementation may impair exercise performance by enhancing the formation of SNO, thus reducing NO bioavailability [113]. Further studies are needed to be elucidated the exact influence of possible interactions.…”
Section: Uncertainties On the Use Of N-acetylcysteine As An Antioxidant Supplementmentioning
confidence: 99%